2015
DOI: 10.1016/j.smallrumres.2015.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and pathogen load of Cryptosporidium and Giardia in sheep faeces collected from saleyards and in abattoir effluent in Western Australia

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
3
1
Order By: Relevance
“…Our findings further showed that the prevalence of G. duodenalis was 4.0% and 4.3% in sheep and goats, respectively. These results are consistent with many previous studies in Iran and elsewhere [2,[32][33][34][35][36][37]. In two previous Iranian studies, the prevalence of G. duodenalis was estimated at 6.2% (12/192) in sheep, and at 5.0% (5/100) in goats in Yazd [29].…”
Section: Discussionsupporting
confidence: 92%
“…Our findings further showed that the prevalence of G. duodenalis was 4.0% and 4.3% in sheep and goats, respectively. These results are consistent with many previous studies in Iran and elsewhere [2,[32][33][34][35][36][37]. In two previous Iranian studies, the prevalence of G. duodenalis was estimated at 6.2% (12/192) in sheep, and at 5.0% (5/100) in goats in Yazd [29].…”
Section: Discussionsupporting
confidence: 92%
“…In sheep, assemblage E was identified in 79.5% of positive isolates typed, while assemblage A was identified in 20.5% of faecal samples positive for G. duodenalis. With the exception of one study conducted on sheep in Victoria, which reported a higher prevalence of assemblage A J o u r n a l P r e -p r o o f compared to assemblage E in sheep (Nolan et al, 2010), all other studies reported that assemblage E was the dominant assemblage in Australian sheep (McCarthy et al, 2008;Yang et al, 2009;Sweeny et al, 2011;Yang et al, 2014;Yang et al, 2015). In the present study, all the sheepderived assemblage E sequences were identical and all clustered into a sheep cluster.…”
Section: Discussioncontrasting
confidence: 69%
“…and this will require further studies [159]. The prevalence of the infection in sheep, using quantitative multiplex PCR, in 474 fecal samples from 2 sales yards on 4 occasions and 96 effluent samples, was 6.5% with the zoonotic species C. parvum and C. ubiquitum accounting for 54.2% of the positive samples [160].…”
Section: Australiamentioning
confidence: 99%